2014
DOI: 10.1186/1478-7954-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survival for Aboriginal and Torres Strait Islander Australians: a national study of survival rates and excess mortality

Abstract: BackgroundNational cancer survival statistics are available for the total Australian population but not Indigenous Australians, although their cancer mortality rates are known to be higher than those of other Australians. We aimed to validate analysis methods and report cancer survival rates for Indigenous Australians as the basis for regular national reporting.MethodsWe used national cancer registrations data to calculate all-cancer and site-specific relative survival for Indigenous Australians (compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 10 publications
3
97
0
Order By: Relevance
“…The cervical cancer incidence is approximately 2 times higher (20 vs 9 per 100,000) and the mortality rates are 4 times higher (8 vs 2 deaths per 100,000) for Indigenous women versus non‐Indigenous women 1. Indigenous women are more likely to have advanced disease when they are diagnosed3 and lower survival rates than non‐Indigenous women (5‐year survival rate, 57.6% vs 78.3%) 4…”
Section: Introductionmentioning
confidence: 99%
“…The cervical cancer incidence is approximately 2 times higher (20 vs 9 per 100,000) and the mortality rates are 4 times higher (8 vs 2 deaths per 100,000) for Indigenous women versus non‐Indigenous women 1. Indigenous women are more likely to have advanced disease when they are diagnosed3 and lower survival rates than non‐Indigenous women (5‐year survival rate, 57.6% vs 78.3%) 4…”
Section: Introductionmentioning
confidence: 99%
“…12 There is also evidence that survival differences between Australian Indigenous and non-Indigenous cancer patients are most prominent in the first years following diagnosis. 13,14 No study has comprehensively explored the demographic and clinical factors that may explain poorer survival among Australian Indigenous gynecologic cancer patients. This article assesses the factors associated with 1-and 5-year survival rates for Indigenous compared with non-Indigenous women diagnosed with a gynecologic cancer in Queensland.…”
mentioning
confidence: 99%
“…The Indigenous relative survival analysis for lung cancer over years 2001-2007 was significantly lower than nonIndigenous cases (age adjusted to age distribution of non-Indigenous cases). 56 Research has also found that the survival difference for Indigenous Australians with cancer compared to non-Indigenous was mostly during the first year after diagnosis. 6,56 5 There is evidence however, that suggests a higher incidence of fatal Indigenous Non-Indigenous…”
Section: Epidemiology Of Lung Cancermentioning
confidence: 99%
“…These two factors contribute to the cause of poor outcomes. 56 Remoteness of residence also contributes to poor cancer outcomes but whether non-Indigenous cancer patients living in similar demographic and socio-economic circumstances have similar outcomes needs to be more fully investigated.…”
Section: Epidemiology Of Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation